Clinical significance of visceral adiposity assessed by computed tomography: A Japanese perspective - Ryo, Miwa (Baishideng Publishing Group Inc, 2014)
Abdominal obesity, rather than total amount of fat, is linked to obesity-related disorders. Visceral adiposity is an important component of obesity-related disorders in Japanese individuals with a mild degree of adiposity compared with Western subjects. In 1983, our group reported techniques for body fat analysis using computed tomography (CT) and established the concept of visceral fat obesity in which intra-abdominal fat accumulation is an important factor in the development of obesity-related complications, such as diabetes, lipid disorders, hypertension and atherosclerosis. Our group also established ideal imaging conditions for determining abdominal fat area at the umbilical level CT scan. Visceral fat area (VFA) measured in a single slice at L4 level correlated significantly with the total abdominal visceral fat volume measured on multislice CT scan. In a large-scale study of a Japanese population, the mean number of obesity-related cardiovascular risk factors (hypertension, low high-density lipoprotein cholesterolemia and/or hypertriglyceridemia, and hyperglycemia) was greater than 1.0 at 100 cm(2) of VFA, irrespective of gender, age and body mass index. Our group also demonstrated that reduction of visceral fat accumulation subsequent to voluntary lifestyle modification, “Hokenshido”, correlated with a decrease in the number of obesity-related cardiovascular risk factors. It is important to select the most appropriate subjects from the general population (e.g., non-obese subjects with a cluster of risk factors for the metabolic syndrome) that are most suitable for body weight reduction, with the goal of preventing atherosclerotic cardiovascular diseases.